PENGEMBANGAN MEDIA PERMAINAN SAINS DI SENTRA BAHAN ALAM PADA KELOMPOK B - Taopik Rahman; Edi Hendri Mulyana; Esi Destri Fathirahmah (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2020)
This research is based on the limitations of learning media in natural materials centers. Science game media as an alternative learning media according to children's characteristics. The purpose of this study was to produce a product for the development of science game media at the center of natural ingredients in group B on children's learning outcomes. This research uses a development-based method, namely the McKenney & Reeves EDR (Educational Design Research) model with three stages: 1) analysis and exploration, 2) product design development, and 3) product evaluation and reflection. The technique of collecting data by conducting interviews, observation, and questionnaires. The data analysis uses data reduction, display data, and conclusion drawing / verification. The effectiveness of the product in the phase 1 trial, most of the children responded positively to the effectiveness of learning outcomes with an average percentage of 82.86%. Then make revisions related to recommendations from teachers to correct deficiencies in these products so that they become more optimal. After that, the phase 2 trial was conducted again, with most children giving a positive response to the effectiveness of children's learning outcomes with an average percentage of 95.59%. Based on these results, seen from the percentage of the results of the first and second stage trials, it increased by 11% and showed that the development of science game media in natural materials centers in group B was feasible to be used in the learning process. Penelitian ini didasari oleh keterbatasan media pembelajaran di sentra bahan alam. Media permainan sains sebagai alternatif media pembelajaran sesuai karakteristik anak. Tujuan penelitian ini untuk menghasilkan produk pengembangan media permainan sains di sentra bahan alam pada kelompok B terhadap hasil belajar anak. Penelitian ini menggunakan metode berbasis pengembangan yaitu EDR (Educational Design Research)model McKenney & Reeves dengan tiga tahap: 1) analisis dan eksplorasi, 2) pengembangan desain produk, serta 3) evaluasi dan refleksi produk. Teknik pengumpulan data dengan melakukan wawancara, observasi, dan angket/kuisioner. Adapun analisis datanya menggunakandata reduction(mengorganisir data), data display(membuat uraian terperinci), dan conclusion drawing/verification(melakukan interpretasi dan kesimpulan). Keefektifitasan produk pada uji coba tahap 1, sebagian besar anak memberikan respon positif efektifitas hasil belajar dengan rata-rata persentase 82,86%. Kemudian melakukan revisi terkait rekomendasi dari guru untuk memperbaiki kekurangan produk tersebut supaya menjadi lebih optimal. Setelah itu dilakukan lagi uji coba tahap 2, dengan sebagian besar anak memberikan respon positif efektifitas hasil belajar anak dengan rata-rata persentase 95,59%. Berdasarkan hasil tersebut, dilihat dari persentase hasil uji coba tahap 1 dan 2 meningkat sebesar 11% dan menunjukan bahwa pengembangan media permainan sains di sentra bahan alam pada kelompok B layak untuk digunakan dalam proses pembelajaran.